Ocular health among industrial workers: a prevalence study of foreign body injury, refractive error, dry eye, pterygium and pingueculae - Ay, İbrahim Ethem; Demirezen, Murat; Şenol, Yiğit; Til, Ayşen (La Medicina del Lavoro, 2022)
Background: Workplaces play a critical role in developing ocular diseases, owing to the risk of accidents. This study aimed to evaluate the ocular health of industrial workers by determining the prevalence of foreign body injury, refractive error, dry eye, and pterygium/pingueculae, as well as the factors influencing these diseases. Methods: This study involved on-site examinations of workers from an industrial area hosting marble processing factories and metal sectors. Data such as refractive error, foreign body injury-related corneal nephelium, pterygium/pingueculae presence, and Schirmer test-assisted dry eye evaluation were all collected. Results: The average age of workers was 35.78±10.05 years, with a female-to-male ratio of 20:220. The majority of workers had completed primary school (56.3%), smoked >1 cigarette/day (57.6%), and did not use any assistive devices for bodily functions (88.3%). On average, working hours/week were 55.07±8.79, and working years were 5.99±7.00. Dry eyes were found in 31 (22%), and 35 (34%) marble and metal workers, respectively (p=0.042). 11 (7.9%) marble workers and 29 (28%) metal workers had foreign body ocular injury-related corneal nephelium (p=0.0001). Furthermore, pterygium/pingueculae were revealed in 17 marble workers (12.3%) and three metal workers (3%) (p=0.009). Conclusions: Ocular health is essential, and routine ocular health screening in industrial workers, as well as workplace safety measures, should be implemented to prevent potential occupational accidents.